La légende de Raphaël. Les « grandes » et les « petites » vies d’une figure exemplaire de l’art, écrites en France au cours du XIXe siècle - Dubreuil-Blondin, Nicole (RACAR : Revue d'art canadienne / Canadian Art Review, 1995)
Considering the lives of Raphael written in nineteenth-century France, this article examines the epistemological status and the ideological function of an important genre of art historical writing: the artist monograph. During a period characterized by new scientific ambitions and by the development of the discipline within academic institutions, the Vasarian model of the vita undergoes a number of changes that do not, however, alter in a significant way its celebrational purpose. Especially throughout the biographical anecdotes that sustain the narrative of his famous career (like the episode of his love affair with la Fornarina), Raphael remains both the great man and the angelic figure concocted by tradition, combining pagan and Christian standards of excellence, a pattern that finds itself repeated in the more popular versions of Raphael's lives, whether written for educational or for recreational purposes. The success story proposed by the life of Raphael – one of the artists most written about in France between 1800 and 1900 – establishes a poignant contrast with the destiny of the modern artist elaborated in contemporary literature, under the aegis of bohemia. It suggests that art history likes winners and not losers and that the genre of the artist monograph always serves some ideological purpose, like compensating fantasmatically for the economic, social and political insecurities of the times.